2007
DOI: 10.1007/s10551-007-9483-4
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Creativity and Innovation without Encouraging Unethical Behavior

Abstract: ethics, ethical organizations, creativity, innovation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(106 citation statements)
references
References 32 publications
3
97
0
6
Order By: Relevance
“…In particular, this study confirms that the ethical culture of an organisation matters when the organisation's desired outcome is innovativeness (cf. Baucus et al, 2008;Ruppel and Harrington, 2000;Riivari et al, 2012).…”
Section: Insert Table V Herementioning
confidence: 99%
See 2 more Smart Citations
“…In particular, this study confirms that the ethical culture of an organisation matters when the organisation's desired outcome is innovativeness (cf. Baucus et al, 2008;Ruppel and Harrington, 2000;Riivari et al, 2012).…”
Section: Insert Table V Herementioning
confidence: 99%
“…However, even if the importance of innovativeness to the success of an organisation has been generally recognised, researchers rarely discuss ethical themes, even though increasing innovation in an organisation may raise ethical considerations. One exception to this is a literature review by Baucus et al (2008), who found that ethical issues like high risk-taking, breaking rules and challenging authority can be problematic in fostering creativity and innovation. The study by Baucus et al (2008) supports the idea that more attention should be paid to ethics also when topics related to innovation and creativity are studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A person's ability to experiment is crucial for team's performance and new product development, as prototypes (from experimentation) enable more powerful explanation via solution visualization and successful idea evolving (West & Iansiti, 2003;Wouters & Roijmans, 2010). Second, risk-taking involves taking bold actions, and is also an important factor that positively affects creativity in terms of idea boldness ( Baucus, Norton, Baucus, & Human, 2008), firm performance (Antoncic, 2003), and team innovation performance (particularly radical innovation due to higher level of complexity and uncertainty) (Cabrales, Medina, Lavado, & Cabrera, 2008;Rhee, Park, & Lee, 2010). Moreover, experimentation and trial and error learning improve the development process and foster creativity and organizational innovation performance (Cannon & Edmondson, 2005;Thomke, 2003).…”
Section: The Experimentermentioning
confidence: 99%
“…However, despite the recognition of organisational culture as a factor influencing organisational capability to innovate, there is still little agreement on the type of organisational culture that helps organisations to be innovative (Büschgens et al, 2013) organisational context that motivates employees to engage in exploration and experimenting, knowledge sharing and creation and, thus, account for innovation development (Ellonen et al, 2008;Sankowska, 2013). However, the capability to innovate includes a risk-taking component, which may sometimes prompt individuals to think and act innovatively yet irresponsibly and unfairly to others, disregarding the long-term perspectives of organisational development and society (Baucus et al, 2008;Gino and Ariely, 2011). Therefore, urge for organisational innovativeness in public organisations has ethical implications (Jordan, 2013).…”
Section: Introductionmentioning
confidence: 99%